2014
DOI: 10.7717/peerj.580
|View full text |Cite
|
Sign up to set email alerts
|

Case based rubella surveillance in Abia State, South East Nigeria, 2007–2011

Abstract: Introduction. Rubella infection has the potential of causing severe fetal birth defects collectively called congenital rubella syndrome (CRS) if the mother is infected early in pregnancy. However, little is known about rubella and CRS epidemiology in Nigeria and rubella vaccines are still not part of routine childhood immunization in Nigeria.Methods. Analysis of confirmed cases of rubella in Abia State, Nigeria from 2007 to 2011 detected through Abia State Integrated Disease Surveillance and Response system.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
12
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 10 publications
6
12
1
Order By: Relevance
“…This was in agreement with previous findings from Ethiopia [11], Nigeria [12], and Kenya [14]. In an outbreak report from Poland, young male adults were the most affected [15].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This was in agreement with previous findings from Ethiopia [11], Nigeria [12], and Kenya [14]. In an outbreak report from Poland, young male adults were the most affected [15].…”
Section: Discussionsupporting
confidence: 93%
“…The proportion of rubella positive cases increased from 4.2% (83) in 2009 to 23.9% (856) in 2013 but dropped to 10.6% (222 cases) and 15.3% (319 cases) in 2014 and 2015 respectively. This was higher than previous findings from Ethiopia [11] and Abia State of Nigeria [12] and was lower than a finding of 37.6% from Zimbabwe [13]. The increasing number of laboratory confirmations might be related with improvement in surveillance sensitivity, quality and coverage.…”
Section: Discussioncontrasting
confidence: 71%
“…In 2-dose measles-mumps-rubella (MMR) vaccine coverage, a third dose of MMR vaccine had been demonstrated to be safe and important in fighting and preventing measles outbreak [ 21 ]. A study in Abia state [ 22 ] showed the need to use measles-mumps-rubella (MMR) vaccine in place of measles vaccines alone during childhood immunization. Safe and effective vaccination programme is, therefore, a function of many factors especially effective cold chain maintenance [ 8 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another vein, one of the few studies done in Nigeria, precisely, in Abia State, southeastern Nigeria showed an incidence of new rubella infection of 6.81/1,000,000 population in 2007 which decreased to 2.28/1,000,000 in 2009, but soared to 6.34/1,000,000 in 2011[ 10 ]. According to the study, the reason for the decrease in 2009 was not clear since there is no routine rubella vaccination in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…According to the study, the reason for the decrease in 2009 was not clear since there is no routine rubella vaccination in Nigeria. The authors argued that the decrease could be due to inadequate rubella surveillance activity [ 10 ]. Eighty six percent of the new rubella cases occurred in children who were younger than 15 years old.…”
Section: Introductionmentioning
confidence: 99%